2021
DOI: 10.1371/journal.pgen.1009233
|View full text |Cite|
|
Sign up to set email alerts
|

Runx1 is a central regulator of osteogenesis for bone homeostasis by orchestrating BMP and WNT signaling pathways

Abstract: Runx1 is highly expressed in osteoblasts, however, its function in osteogenesis is unclear. We generated mesenchymal progenitor-specific (Runx1f/fTwist2-Cre) and osteoblast-specific (Runx1f/fCol1α1-Cre) conditional knockout (Runx1 CKO) mice. The mutant CKO mice with normal skeletal development displayed a severe osteoporosis phenotype at postnatal and adult stages. Runx1 CKO resulted in decreased osteogenesis and increased adipogenesis. RNA-sequencing analysis, Western blot, and qPCR validation of Runx1 CKO sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 46 publications
1
83
0
1
Order By: Relevance
“…The top downregulated gene clusters were associated with fatty acid biosynthetic process , fatty acid metabolic process , lipid metabolic process and so on ( Figure 2A ), which were all closely associated with adipocyte differentiation. To find out the target genes of lnc-FR332443 in adipocyte differentiation, we analyzed the potential transcription factors of lnc-FR332443 and found that Runx1 which had been previously shown in the negative regulation of adipogenesis ( Tang et al, 2021 ) is among them ( Supplementary Material 2 ). Further we analyzed mRNA expression in the F72h mouse and control mouse mWAT using microarrays and measured 1,353 downregulated mRNAs and 494 upregulated mRNAs (fold change > 2, P < 0.05) ( Figure 2B ) among the total 33,420 mRNAs ( Supplementary Material 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The top downregulated gene clusters were associated with fatty acid biosynthetic process , fatty acid metabolic process , lipid metabolic process and so on ( Figure 2A ), which were all closely associated with adipocyte differentiation. To find out the target genes of lnc-FR332443 in adipocyte differentiation, we analyzed the potential transcription factors of lnc-FR332443 and found that Runx1 which had been previously shown in the negative regulation of adipogenesis ( Tang et al, 2021 ) is among them ( Supplementary Material 2 ). Further we analyzed mRNA expression in the F72h mouse and control mouse mWAT using microarrays and measured 1,353 downregulated mRNAs and 494 upregulated mRNAs (fold change > 2, P < 0.05) ( Figure 2B ) among the total 33,420 mRNAs ( Supplementary Material 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the essential functions of Runx1 in many biological programs related to development ( Ichikawa et al, 2004 ) and our previous research results that Runx1 could cell autonomously and cell non-autonomously regulate adipocyte differentiation ( Tang C.Y. et al, 2020 ; Tang et al, 2021 ), we hypothesized that Runx1 might be involved in the process of fat formation in the WAT of the AAV-Lnc-FR332443 mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations